ANALYZING THE IMPACT OF COMPENSATION AND LEADERSHIP ON EMPLOYEE PRODUCTIVITY AT CV RAJAWALI MAMASA - Musrang Musrang; Andi Indra Martini; Suharlina Suharlina (Jurnal Ekonomi, 2023)
This research, conducted at CV. Rajawali Mamasa, aimed to investigate the impact of compensation and leadership styles on employee productivity. The study utilized both primary and secondary data sources, including surveys and direct observations. The findings reveal significant positive effects of compensation and leadership on employee productivity. Specifically, adequate compensation, including salaries, allowances, and incentives, was found to boost employee performance. Moreover, effective leadership styles, such as authoritative, democratic, and participative leadership, were shown to motivate employees to work more efficiently.